Sequential Convex Programming Methods for Solving Large Topology Optimization Problems: Implementation and Computational Results (Journal of Computational Mathematics, 2005)
In this paper, we describe a method to solve large-scale structural optimization problems by sequential convex programming (SCP). A predictor-corrector interior point method is applied to solve the strictly convex subproblems. The SCP algorithm and the topology optimization approach are introduced. Especially, different strategies to solve certain linear systems of equations are analyzed. Numerical results are presented to show the efficiency of the proposed method for solving topology optimization problems and to compare different variants.
Keywords: Large scale optimization; Topology optimization; Sequential convex programming method; Predictor-corrector interior point method; Method of moving asymptotes.